The Technology of Educational Games for Support Science Learning: A Preliminary Study - Suritno Fayanto; Dwi Sulisworo; Wa Ode Alkamalia; Wa Ode Indrawati; Hunaidah Hunaidah (J I M P - Jurnal Informatika Merdeka Pasuruan, 2021)
Many learning technologies have emerged in education, often called educational games, along with technological development. Educational games are one of the learning technology instruments to support student interest. Educational games have exciting features that make students more interested in learning, especially science. Educational games in science learning give a different nuance to the learning process—this distinction is formed in a system that can attract students' interest and attention. This paper is here to provide an overview of the importance of educational games in science learning. Students usually consider learning science unattractive because it involves thinking and counting processes. Learning science by presenting a new system in educational games turns out to have its nuances. In science learning, educational games are presented in quizzes or games. This study uses qualitative research on review articles sourced from journals and books. Researchers use journals, both national and international journals, as the main reference source in conducting research. The analysis results found that each student can raise the level of the game if they can solve the given scientific problem. Therefore, educational games support learning in the classroom so that the learning process is more fun.Keyword— educational games, kahoot, quizizi, quizlet, games-based learning